TOPICAL ASPECTS REGARDING THE REMODELING OF THE TEMPOROMANDIBULAR JOINT AS AN INDIVIDUAL BIOLOGICAL PHENOMENON IN MAXILLOFACIAL SURGERY - Mihai Constantin; Doriana Agop Forna; Constantin Budacu (Romanian Society of Oral Rehabilitation, 2019)
The health condition of the stomatognathic system implies a morpho-functional integrity and harmonious, proportional development of its constitutive parts, so that the relationships between teeth, arches and maxillaries should remain within the limits of certain "phylogenetic" variables and their functioning should be automatically coordinated, through a fully operational regulation system. Considered to be the most complex articulation of the human body, the temporomandibular joint is, at the same time, one of the main components of the stomatognathic system, contributing to the fulfilment of certain basic functions of it: mastication, deglutition, phonation. The modification of the articular movement patterns and the micro-traumatisms that appear in case of certain dysfunctions of periodontal, dental or neuromuscular origin make the temporomandibular joint one of the elements of the stomatognathic system most frequently affected within the dysfunctional syndrome. Material and method: The statistical study was carried out on a lot of 69 patients, out of which 42 cases (60.86%) were diagnosed with open traumatic lesions in the temporomandibular joint and 27 cases (39.14%) had recurring lesions in the period from 2013 to 2017. Results and discussions: When the traumatism caused extended lesions on the bone heads and the meniscus, there are favorable conditions for an ankylosis to set it. Conclusions: Peri-articular lesions of the soft tissues, especially of the elevator muscles of the mandible, can be followed by retractile scars that eventually lead to mandible constriction.